Hemen hemen asal idealler ve zayıf asal idealler - Karacan, Emine Serap (My University, 2017)
HEMEN HEMEN ASAL İDEALLER VE ZAYIF ASAL İDEALLER Tezimizin amacı yeni tip ideal yapılarını özellikleriyle birlikte tanıtmaktır. Bunun için öncelikle ideal tanımı verilmiştir. Bu yeni tip ideal yapıları asal ideal ve asalımsı ideal başlıkları altında incelenmiştir. İkinci kısımda zayıf asal idealler ve hemen hemen asal idealler, asal idealler başlığı altında tanımlanmıştır. Bu idealler çeşitli halka yapıları altında incelenmiştir. Son kısımda ise zayıf asalımsı idealler ve hemen hemen asalımsı idealler, asalımsı idealler başlığı altında tanımlanmıştır.

ALMOST PRIME IDEALS AND WEAKLY PRIME IDEALS In this study our main purpose is to introduce the structures of various ideals with their properties. For this, firstly, we give the definition of “ideal”. And we investigate these ideals in domains of “Prime Ideals” and “Primary Ideals”. If we give some details, we survey “Almost Prime Ideals” and “Weakly Prime Ideals” in domain of “Prime Ideals”. Furthermore, we present these ideals with structures of different rings. Finally, we examine “Almost Prime Ideals” and “Weakly Prime Ideals” in domain of “Prime Ideals”
Keywords: Hemen hemen asal idealler; İdealler; Matematik; Zayıf asal idealler